Analisis Reaksi Pasar dan Risiko Investasi antara Perusahaan Perata Laba dan Buka Perata Laba - Noviant, Brahm Ardhi; Marsono, Marsono (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2013)
The research aims to: 1) Analyzing is there any difference of market reaction between incomesmoothers and non income smoothers companies. 2) Analyzing is there any difference of investmentrisk between the income smoothers and non income smoothers companies. The research was doneto manufactures companies listed in BEI. Among 149 manufactures companies listed in BEI, 48companies were taken to become sample. Using Eckel Index, the sample were divided into twotype, 9 income smoothers and 39 non income smoothers. Documentation technique was used togather data. Independent sample t-test was used to analyzed data if it has normal distribution inKolmogorov-Smirnov test. The result show that there was no difference of the market reactionbetween income smoothers and non income smoothers companies, and there was no differenceof investment risk between income smoothers and non income smoothers companies. It’s becausethe result of independent sample t-test show the probability of amount market reaction andinvestment risk were not significant in 5%.